Genome sequence of the broad host range salmonella bacteriophage phi PVP-SE1 - Santos, Sílvio Roberto Branco (2010)
Salmonella is an important zoonotic pathogen and remains the primary cause of reported food poisoning worldwide with massive outbreaks. The increased resistance of Salmonella to antibiotics and other biocides has encouraged the development of alternatives to chemotherapy such as phage therapy. Phage phi PVP-SE1 is a salmonella phage isolated from a Germany (Regensburg) wastewater plant. This phage is characterized by having a broad lytic spectrum, even broader than Felix 01, being able to infect different Salmonella serotypes of different countries and different origins (food, environmental and clinical). TEM analysis showed a Myoviridae phage having an icosahedral head (84 nm) attached to a contractile tail (120x18 nm) by a connector and presents short fibres. Genome sequencing is of enormous importance for classification of bacteriophages and for understanding their evolution. A full knowledge of phage genome sequences would be helpful to evaluate phage safety for therapy. Moreover, it might allow the identification of useful phage proteins against pathogenic bacteria. Phage PVP-SE1 was sequenced and the genome was found to be terminally redundant and circularly permuted with a size of 145964 bp. The GC content of this phage genome is 45.6% which is slightly lower than its hosts (50%-54%). A total of 244 ORFs were found representing 91.6% (excluding tRNAs) of the full genome. Approximately 46% of encoded proteins are hypothetical and present no homology with any other proteins. Only few of them (22.1%) presented homology with known proteins. Moreover, it was found a large number of genes coding for tRNA (24), 9 promotors, and 7 terminators. The genome sequence presents a high homology (145 gene encoding proteins) with the E. coli bacteriophage rV5. Both phages are unrelated to any other known phage, which might suggest that they belong to a new phage genetic group.